Grafting Helen : the abduction of the classical past - Gumpert, Matthew (University of Wisconsin Press, 2001)
History is a love story: a tale of desire and jealousy, abandonment and fidelity, abduction and theft, rupture and reconciliation. This contention is central to Grafting Helen, Matthew Gumpert's original and dazzling meditation on Helen of Troy as a crucial anchor for much of Western thought and literature.